Ipsilateral Corticospinal Tract Excitability Contributes to the Severity of Mirror Movements in Unilateral Cerebral Palsy: A Case Series. (May 2020) - Rich, Tonya L.; Nemanich, Samuel; Chen, Chao-Ying; Sutter, Ellen N.; Feyma, Tim; Krach, Linda E.; Gillick, Bernadette T.
Mirror movements (MM) can be a clinical manifestation of unilateral cerebral palsy (UCP) causing involuntary movements when attempting to use either hand for functional activities. Atypical development of the corticospinal tract (CST) contributes to impairments in observed motor movements and functional activities. However, little is known about the underlying neurophysiology and contribution of the CST to MM. The current case study characterizes MM in 13 children and young adults with UCP ranging in age from 7 to 19 years and includes clinical and neurophysiologic variables. Clinical profiles included MM of each hand (ie, Woods and Teuber), bimanual coordination and hand use (Assisting Hand Assessment [AHA]), and perception of performance (Canadian Occupational Performance Measure [COPM]). We measured the strength of motor-evoked potentials (MEP) elicited from single-pulse transcranial magnetic stimulation (TMS) of each hemisphere to create a ratio of hemispheric responses. Our sample included three types of CST circuitry: ipsilateral (n = 5), bilateral (n = 3), and contralateral (n = 4). The MEP ratio ranged from 0 to 1.45 (median 0.11) with greater MM observed in participants with ratios greater than 0.5. We observed a positive relationship between the MEP ratio and the more-affected MM score, meaning participants with larger ipsilateral responses from contralesional stimulation (eg, the contralesional hemisphere was stimulated with TMS resulting in an ipsilateral MEP response), as compared with contralateral responses, displayed greater MM than those that did not. There was no relationship between MM and function as measured by the AHA or COPM. These findings suggest a role of the contralesional hemisphere to MM, which could serve as a therapeutic target for interventions.